4D Printing: dawn of an emerging technology cycle. Issue 4 (9th September 2014) - Pei, Eujin
Abstract : Purpose: – The purpose of this article is to reviews state-of-the-art developments in four-dimensional (4D) printing, discuss what it is, investigate new applications that have been discovered and suggest its future impact. Design/methodology/approach: – The article clarifies the definition of 4D printing and describes notable examples covering material science, equipment and applications. Findings: – This article highlights an emerging technology cycle where 4D printing research has gained traction within additive manufacturing. The use of stimuli-responsive materials can be programmed and printed to enable pre-determined reactions when subject to external stimuli. Originality/value: – This article reviews state-of-the-art developments in 4D printing, discusses what it is, investigates new applications that have been discovered and suggests its future impact.